Demokrasi dan Pendidikan Islam: Menuju Rekonstruksi Sistem Pembelajaran di Sekolah - Erlan Muliadi (Universitas Islam Negeri (UIN) Mataram, 2019)
It must be recognized that there is a tendency for schools as an institution to often use the prestige attached to it to deny democratic values ??in the learning process. In accordance with the object of this study, this type of research is included in the category of library research, namely, first, by recording all findings regarding general consumption motivation in each study discussion obtained in the literature and sources, and or invention. The reality of the world of Islamic education which emphasizes aspects of learning that do not pay attention to students has a negative impact on the output of education. Islamic education institutions have so far still adopted traditional educational patterns that have made Islamic education stagnant, which in turn has implications for the Islamic world civilization that is lagging behind other civilizations. Facing the challenge of the changing times of the era which is getting faster then Islamic education should begin to reconstruct traditionalist education patterns which tend to prioritize cognitive aspects, student-centered, towards dialogic-democratic education patterns. The pattern of democratic education is a pattern of education that upholds the development of the potential of students in the direction that will be able to give color to world civilization. Abstrak: Terdapat kecenderungan sekolah-sekolah sebagai sebuah institusi yang sering menggunakan prestise yang melekat padanya untuk mengingkari nilai-nilai demokrasi dalam proses pembelajaran. Sesuai dengan obyek kajian ini, maka jenis penelitian ini termasuk dalam kategori penelitian kepustakaan (library research), yaitu, pertama, dengan mencatat semua temuan mengenai motivasi konsumsi secara umum pada setiap pembahasan penelitian yang didapatkan dalam literatur-literatur dan sumber-sumber, dan atau penemuan. Realitas dunia pendidikan Islam yang mengedepankan aspek pembelajaran yang kurang memperhatikan peserta didik telah memberi dampak buruk bagi out put pendidikannya. Lembaga pendidikan Islam selama ini masih mengadopsi pola pendidikan tradisional sehingga menjadikan pendiidkan Islam stagnan, yang selanjutnya berimplikasi pada peradaban dunia islam yang tertinggal dari peradaban lain. Menghadapi tantangan arus perubahan zaman yang semakin cepat maka pendidikan Islam sudah seharusnya mulai merekonstruksi pola pendidikan tradisionalis yang cenderung mengedepankan aspek kognitif, student centered, menuju pola pendidikan dialogis-demokratis. Pola pendidikan demokratis adalah merupakan pola pendidikan yang menunjung berkembangnya potensi siswa menuju arah yang nantinya mampu memberikan warna bagi peradaban dunia.